2022
DOI: 10.1186/s12885-022-10141-1
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable lifestyle factors have a larger contribution to colorectal neoplasms than family history

Abstract: Background  Screening recommendations for colorectal cancer (CRC) are mainly based on family history rather than lifestyle risk factors. We aimed to assess and compare risk factors for colorectal neoplasm (CRN) and evaluate trends in neoplasm detection rates during the three rounds of screening from 2012 to 2020 in Tianjin, China. Methods This study was based on 89,535 first-recorded colonoscopies in Tianjin CRC screening program, 2012–2020. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(78 reference statements)
0
2
0
1
Order By: Relevance
“…However, the social stigma associated with bowel cancer affects the accuracy of reporting a family history of CRC [5][6][7][8][9][10][11], as also reported in southern Taiwan [12]. However, many studies have shown that modifiable lifestyle factors including smoking, alcohol consumption, physical activity, and body mass index contribute more to CRC than family history [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the social stigma associated with bowel cancer affects the accuracy of reporting a family history of CRC [5][6][7][8][9][10][11], as also reported in southern Taiwan [12]. However, many studies have shown that modifiable lifestyle factors including smoking, alcohol consumption, physical activity, and body mass index contribute more to CRC than family history [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, CRC has also been reported as the third most common cancer; more than 7000 new cases were reported in the Swedish Colorectal Cancer Registry in 2021 (40). Lifestyle factors, including poor diet, smoking, alcohol consumption, a lack of physical activity, and an increasing prevalence of obesity, play a significant role in the development of CRC (41). Cancer survival is highly dependent on the stage at diagnosis.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Badanie przeprowadzone w Malezji sugeruje, że przez zmianę stylu życia można było zapobiec około 18% przypadków stwierdzonych tam w 2013 roku [10]. W Chinach przeprowadzono badanie wskazujące, że 29% zaawansowanych nowotworów jelita grubego u mężczyzn i 13,8% u kobiet można powiązać z modyfikowalnymi czynnikami ryzyka [11]. Poniżej omówione są najbardziej znane z tych czynników.…”
Section: Modyfikowalne Czynniki Ryzykaunclassified